2013
DOI: 10.1002/ejlt.201300072
|View full text |Cite
|
Sign up to set email alerts
|

What are the trans fatty acids issues in foods after discontinuation of industrially produced trans fats? Ruminant products, vegetable oils, and synthetic supplements

Abstract: Adverse health effect of trans fatty acids (TFAs) are well recognized , which has precipitated efforts to reduce their content in food products. With the decline of dietary TFAs derived from partial oil hydrogenation, interest is focused on the remaining sources of dietary TFAs derived from ruminants (rTFA), deo-dorized vegetable oils, trans isomerization during frying, and synthetic conjugated FA (CFA) supplements. Partial hydro-genation and heat-treated oils result in a random distribution of TFA isomers, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
84
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(88 citation statements)
references
References 156 publications
(300 reference statements)
2
84
0
2
Order By: Relevance
“…It has been shown that 18:1 trans-10 is produced in an alternate biohydrogenation route when high-concentrate diets are used (Bessa et al 2005) and our data are fully consistent with this. The occurrence of elevated 18:1 trans-10 concentrations in meat is characteristic of intensive finishing systems for beef cattle and the putative negative health effects of 18:1 trans-10-enriched meats are currently under discussion (Aldai et al 2013). …”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that 18:1 trans-10 is produced in an alternate biohydrogenation route when high-concentrate diets are used (Bessa et al 2005) and our data are fully consistent with this. The occurrence of elevated 18:1 trans-10 concentrations in meat is characteristic of intensive finishing systems for beef cattle and the putative negative health effects of 18:1 trans-10-enriched meats are currently under discussion (Aldai et al 2013). …”
Section: Discussionmentioning
confidence: 99%
“…The reason for that were the changes in biohydrogenation pathways, resulting in the replacement of t11-18:1 by t10-18:1 as the major biohydrogenation intermediate (hereafter t10-shift), observed when the Cistus and oil increased in the diet. The occurrence of the t10-shift has been frequently reported in ruminants fed low-forage, high-oil diets (Aldai et al, 2013) and in growing ruminants raised on pasture and supplemented with ground corn (Rosa et al, 2014). Polyunsaturated FA intake has a profound and well established effect on the accumulation of biohydrogenation intermediates in rumen and tissues (Shingfield et al, 2013;Shingfield and Wallace, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In the present experiment, despite a middle dietary forage inclusion (50%), the Cistus tannins increased mostly the t10-18:1 in NL, with no effect on t11-18:1. The synergy between PUFA and tannins intake promoting the t10-shift is undesirable, assuming that t10-18:1 has deleterious health effects to consumers, as reviewed by Aldai et al (2013) and is not a substrate for endogenous CLA synthesis. Despite the exuberant t10-18:1 increase in NL, oil supplementation also increased t11-18:1, but not c9,t11-18:2.…”
Section: Discussionmentioning
confidence: 99%
“…Sin embargo, la carne y los productos cárnicos son alimentos que en la actualidad están en entredicho debido a que no todas las grasas tipo trans de origen animal, y en particular las de los rumiantes, presentan efectos adversos sobre la salud humana Roy et al, 2007;Burnyeat, 2015). Como se ha constatado en varios trabajos de revisión (Aldai et al, 2013;Bessa et al, 2015) su perfil lipídico está marcadamente influenciado por la alimentación del animal.…”
Section: Introductionunclassified